Influences of Online Learning Environment on International Students’ Intrinsic Motivation and Engagement in the Chinese Learning - Zang, Fengxiang; Tian, Mei; Fan, Jingwei; Sun, Ying (Journal of International Students, 2022)
With the impact of the COVID-19 pandemic, Chinese teaching for international students in Chinese universities has largely moved online. Despite the comprehensive literature regarding the influences of environmental factors on domestic students’ learning in traditional learning environment, few studies have addressed the influences of online learning environment (OLE) on international students’ Chinese learning experiences. We focus on international students in intensive Chinese courses at a Chinese university, and explores the influences of OLE on these students’ intrinsic motivation (IM) towards and engagement in Chinese learning during the COVID-19 pandemic. Data were collected from an online questionnaire survey and follow-up interviews. The results revealed that the participants had positive perceptions of the online Chinese learning environment, and that the participants had high levels of IM towards and engagement in their Chinese learning. The results  showed the positive impact of the participants’ perceived OLE on their IM  and engagement in Chinese learning.